PROJETO DE INCENTIVO AO ATENDIMENTO DO ENFERMEIRO NO CUIDADO A GESTANTES E PUÉRPERAS NA UNIDADE BÁSICA DE SAÚDE CAMPO NOVO SANTA INÊS- MA - Silva, Vilma Marques (2013)
When considering the cultural patterns and processes of socialization of women and the power of (the) professional service providers in the clinic, we can identify mechanisms, actions and attitudes that reinforce the exclusion of women present in these services, especially when that user a woman with low socioeconomic status. In general, women pregnant or postpartum women, need to care about their health, is not consulted or even heard, with the justification of the urgent need of care. The significance of early weaning for women in which most of them refer undergo difficulty, uncertainty, fear and doubt regarding breastfeeding noting that the difficulties could partly be minimized through access to adequate assistance or puerperium 've even during pregnancy reinforce the development of this action plan.